Optimizing treatment for depressed parents of children with emotional and behavioral disorders: A multi-site feasibility trial - Brendan F. Andrade; Sabrina Brodkin; Aliza Israel; Tatiana Valverde da Conceicao; Madison Aitken; Tatiana Djurovic; Marco Battaglia; Anne-Claude Bedard; Anjali Suri; Darren Courtney; Hali Kil; Stefan Kloiber; et al. (PLoS ONE, 2026)
Background Behavioral parent training (BPT) programs are effective for reducing disruptive behavior of many children with emotional and behavioral disorders (EBD) and improving skills and competencies of their parents. However, these interventions are not sufficiently effective for parents who themselves have depression. This study assessed the feasibility of the Addressing Depression and Positive Parenting Techniques (ADAPT) Program—a novel BPT that includes aspects of cognitive behavioral therapy and dialectical behavior therapy. We identified whether recruitment was possible, attendance was acceptable, participants were satisfied, and facilitators adhered to the protocol. Additionally, we measured trends in changes in parent and child outcomes with intervention. Methods Participants were 28 parents and their children with EBD, referred to two hospital-based clinics. Parents were eligible if they (1) had a child aged 6–10 experiencing emotional and behavioral difficulties and (2) were experiencing elevated depressive symptoms. ADAPT took place virtually over 10 weeks. Participants completed measures before, weekly and after treatment. Clinicians recorded attendance and completed weekly treatment fidelity checklists. Results We found that recruitment was possible, the intervention showed high parental satisfaction, and facilitators reported high program fidelity. Further, secondary outcome measures showed evidence of sensitivity to change in the intended direction. Conclusion Given that a priori progression criteria were met and we found preliminary indication of efficacy, we conclude that an RCT of ADAPT to determine efficacy is warranted.